2021
DOI: 10.1051/0004-6361/202039363
|View full text |Cite
|
Sign up to set email alerts
|

SLITRONOMY: Towards a fully wavelet-based strong lensing inversion technique

Abstract: Strong gravitational lensing provides a wealth of astrophysical information on the baryonic and dark matter content of galaxies. It also serves as a valuable cosmological probe by allowing us to measure the Hubble constant independently of other methods. These applications all require the difficult task of inverting the lens equation and simultaneously reconstructing the mass profile of the lens along with the original light profile of the unlensed source. As there is no reason for either the lens or the sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Birrer et al 2016Birrer et al , 2019. Most of the time, the source is either pixelised with regularisation applied (Brewer & Lewis 2008;Suyu & Halkola 2010;Nightingale & Dye 2015;Galan et al 2021) or analytical with a main simple profile plus a set of basis functions, such as shapelets, that are designed to capture morphological host complexity beyond axisymmetry (Birrer et al 2015(Birrer et al , 2016(Birrer et al , 2019Birrer & Amara 2018;Shajib et al 2019). Above, we model the source with a circular Sersic profile because we know that this is its true input profile.…”
Section: Influence Of Complexity In the Modelled Sourcementioning
confidence: 99%
“…Birrer et al 2016Birrer et al , 2019. Most of the time, the source is either pixelised with regularisation applied (Brewer & Lewis 2008;Suyu & Halkola 2010;Nightingale & Dye 2015;Galan et al 2021) or analytical with a main simple profile plus a set of basis functions, such as shapelets, that are designed to capture morphological host complexity beyond axisymmetry (Birrer et al 2015(Birrer et al , 2016(Birrer et al , 2019Birrer & Amara 2018;Shajib et al 2019). Above, we model the source with a circular Sersic profile because we know that this is its true input profile.…”
Section: Influence Of Complexity In the Modelled Sourcementioning
confidence: 99%
“…We develop an automated data analysis pipeline that models the distribution of foreground light and mass as a sum of smooth analytic functions, and the background light as either another sum of analytic functions (e.g. Tessore et al 2016), or as a pixellated image (Warren & Dye 2003;Suyu et al 2006;Dye & Warren 2005;Vegetti & Koopmans 2009;Joseph et al 2019;Galan et al 2021). By fitting a mock sample of ∌ 500 lenses we further show that previous versions of PyAutoLens (like many lens fitting algorithms) underestimated the statistical uncertainty of lens model parameters.…”
Section: Introductionmentioning
confidence: 95%
“…Particularly, three separate teams participated in the blind time-delay lens modeling challenge ) using lenstronomy. lenstronomy has seen a substantial development and incorporation of innovations and numerical recipes (Tessore & Metcalf, 2015;Shajib, 2019;Joseph et al, 2019;Galan et al, 2021;, and has found applications beyond its original aim due to the robust and high-standard design requirements.…”
Section: Statement Of Needmentioning
confidence: 99%
“…These open-source affiliated packages effectively create an ecosystem enhancing the capability of lenstronomy. They provide specified and tested solution for specific scientific investigations, such as plug-ins and direct implementation for innovative source reconstruction algorithms (SLITronomy; Joseph et al, 2019;Galan et al, 2021), gravitational wave lensing computations (lensingGW; Pagano et al, 2020), automated pipelines for gravitational lensing reconstruction (dolphin; Shajib et al, 2021a), cluster source reconstruction and local perturbative lens modeling (lenstruction; Yang et al, 2020), enhancement in large-scale structure imaging survey simulations (DESC SLSprinkler; Dark Energy Science Collaboration (LSST DESC) et al, 2021), rendering of sub-halos and line-of-sight halos (pyHalo; Gilman et al, 2020), galaxy morphology analysis (galight; Ding et al, 2020), and hierarchical analyses to measure the Hubble constant (hierArc; . With the rise in popularity and the promises in dealing with ever complex data problems with fast deep-learning methods, dedicated tools for simulating large datasets for applying such methods to strong gravitational lensing (deeplenstronomy; Morgan et al, 2021), (baobab;Park et al, 2021), as well as end-to-end Bayesian Neural Network training and validation packages for Hubble constant measurements (h0rton; Park et al, 2021), and for a hierarchical analysis of galaxy-galaxy lenses (ovejero; Wagner-Carena et al, 2021) have been developed.…”
Section: Ecosystem Of Affiliated Packagesmentioning
confidence: 99%